My losing season - Conroy, Pat. (New York : Bantam Books, 2003)
The author reflects on his days at a South Carolina military college. He recalls his love of basketball and its value to him as a means of self-expression, and shares experiences that shed new light on his novel "The Great Santini.".
Library Journal
Pub Weekly
Wilson's Senior High School
Adult.
Adult
Keywords: Conroy, Pat -- Childhood and youth; Conroy, Pat; Citadel, the Military College of South Carolina; Citadel, the Military College of South Carolina; Basketball players -- South Carolina -- Charleston; College sports -- South Carolina -- Charleston; Failure (Psychology); Novelists, American -- 20th century -- Biography; American novelists -- Biography; Basketball players; College sports -- Charleston (S.C.); Failure (Psychology); Charleston (S.C.) -- Biography; Charleston (S.C.) -- Biography